Mycolicibacterium smegmatis, Basonym Mycobacterium smegmatis, Expresses Morphological Phenotypes Much More Similar to Escherichia coli Than Mycobacterium tuberculosis in Quantitative Structome Analysis and CryoTEM Examination - Yamada, Hiroyuki; Yamaguchi, Masashi; Igarashi, Yuriko; Chikamatsu, Kinuyo; Aono, Akio; Murase, Yoshiro; Morishige, Yuta; Takaki, Akiko; Chibana, Hiroji; Mitarai, Satoshi (Frontiers in Microbiology, 2018)
Abstract Series of structome analyses, that is, quantitative and three-dimensional structural analysis of a whole cell at the electron microscopic level, have been already achieved individually in Exophiala dermatitidis, Saccharomyces cerevisiae, Mycobacterium tuberculosis, Myojin spiral bacteria and Escherichia coli. In these analysis, sample cells were processed through cryo-fixation and rapid freeze-substitution, resulting exquisite preservation of ultrastructures on the serial ultra-thin sections examined by transmission electron microscopy. In this paper, structome analysis of non-pathogenic Mycolicibacterium smegmatis, basonym Mycobacterium smegmatis, was performed. Because M. smegmatis has been often used in molecular biological experiments and experimental tuberculosis as substitute of highly pathogenic M. tuberculosis, it has been a task to compare two species in the same genus, Mycobacterium, in structome analysis. Seven M. smegmatis cells cut into serial ultrathin sections and totally 220 serial ultrathin sections were examined by transmission electron microscopy. Cell profiles were measured, including cell length, diameter of cell and cytoplasm, surface area of outer membrane and plasma membrane, volume of whole cell, periplasm, and cytoplasm, total ribosome number and density per 0.1 fl cytoplasm. These data are based on direct measurement and enumeration of exquisitely preserved single cell structures in the transmission electron microscopy images, not based on the calculation or assumption from biochemical or molecular biological indirect data. All measurement in M. smegmatis except cell length are significantly higher than those of M. tuberculosis. In addition, these data may explain the more rapid growth of M. smegmatis than M. tuberculosis and contribute to understanding of structural properties, which are substantially different from M. tuberculosis, relating to the expression of antigenicity, acid-fastness, and the mechanism of drug-resistance in relation to the ratio of the targets to the corresponding drugs. In addition, data obtained from cryo transmission electron microscopy examination was used to support the validity of structome analysis. Finally, our data strongly support the most recent establishment of the novel genus Mycolicibacterium, into which basonym Mycobacterium smegmatis has been classified.